Predictors of Maternal Depression Management among Primary Care Physicians. (22nd February 2010) - Leiferman, Jenn A.; Dauber, Sarah E.; Scott, Katie; Heisler, Kurt; Paulson, James F.
Abstract : Purpose . The present surveillance study examined predictors of the management of maternal depression in primary care settings. Methods . A total of 217 physicians completed a 60-item survey assessing demographics, physicians' attitudes, beliefs, efficacy, current practices, and perceived barriers regarding the management of maternal depression. Structural equation modeling was used to estimate a model that examined the relationships among physicians' knowledge, beliefs, self-efficacy, perceived barriers, past training toward and current management practices for maternal depression. Results . In a model predicting physician depression management practices, a good overall fit was observed (χ 2 = 136.63, CFI = .97, TLI = .95, RMSEA = .05 ), with physician comfort with, confidence in, and perceived responsibility for managing maternal depression all having prominent positive associations. Conclusions . These findings will guide the development of future multifaceted intervention strategies to enhance physician skills in managing maternal depression in primary care settings.